Characterization of a Temperature-sensitive Mutant of Bacillus subtilis Defective in Deoxyribonucleic Acid Replication - Mendelson, Neil H. (1967)
In this paper we present a preliminary characterization of a temperature-sensitive mutant of Bacillus subtilis which appears to be defective in deoxyribonucleic acid (DNA) replication at high temperature. When log-phase cells of the mutant were transferred from 30 to 45 C, protein synthesis and ribonucleic acid synthesis continued more or less normally for several hours, whereas DNA synthesis continued at a normal rate for only 20 to 30 min and then was drastically reduced. The amount of DNA synthesized prior to this reduction corresponded approximately to the amount of DNA synthesized under conditions of protein synthesis inhibition by the parent or mutant strain. After 1 hr of growth at high temperature, cells of the mutant showed a pronounced drop in viable count. After 30 or 60 min of growth at high temperature, DNA synthesis could be restored by lowering the temperature. A longer period of growth at 45 C led to a loss of reversibility of DNA synthesis. Spores of the mutant synthesized no DNA when germinated at high temperature, although an outgrowing cell appeared. When spores were germinated at low temperature until DNA synthesis began, and then were transferred to high temperature, macromolecular synthesis continued as the log-phase transfer experiments described above.